Equity, diversity, and inclusion in post-secondary student mental health and well-being research: A scoping review protocol - Sandy Rao; Ayomide Olayinka; Rya Buckley; Lexi Ewing; Bilal Qureshi; Thanida Kamchokchai; Khushi Patel; Kristin Cleverley (PLoS ONE, 2026)
Objective The objective of this scoping review is to systematically identify and map the extent, range, and nature of research that explicitly articulates Equity, Diversity, and Inclusion (EDI) within post-secondary student (PSS) mental health and well-being research, and to describe how EDI is conceptualized, operationalized, and implemented across study designs and research processes. Introduction Research addressing PSS mental health and well-being has grown substantially; concurrently, EDI has become a prominent institutional and research priority within post-secondary systems. Despite this convergence, no evidence synthesis has systematically examined how EDI is explicitly integrated into PSS mental health and well-being research. Inclusion criteria This review will include research studies of any design that explicitly articulate EDI within PSS mental health and well-being research. Eligible studies must focus on students enrolled in accredited post-secondary institutions and examine mental health or well-being within post-secondary education contexts. Methods The review will be conducted in accordance with JBI methodology for scoping reviews and guided by the Population–Concept–Context framework. A three-step search strategy will be implemented. Electronic database searches will be conducted in MEDLINE, PsycINFO, CINAHL, EMBASE, ERIC, and Scopus or Web of Science, supplemented by targeted searches of eligible grey literature and reference list screening. Records will undergo title and abstract screening by two independent reviewers, followed by full-text screening. Data will be extracted using a structured, pilot-tested tool designed to capture how EDI is defined, framed, and integrated across stages of the research process. Extracted data will be synthesized using descriptive summary statistics, basic qualitative content analysis, and tabular and graphical mapping to address the review questions. The protocol was developed through sustained engagement with PSS with lived experience of mental health and well-being, including students from equity-deserving groups.